Insights to Chronic Pain in Hernia Repair: Clinicopathological Assessment of Incidence, Predictors, and Long-Term Outcomes in Tertiary Healthcare Settings - Aftab Ahmad Baig; Kaneez Aisha; Waqas Ahmad; Rizwan Khalid; Muhammad Shahid Mehmood; Shaheer Nayyar (Pakistan Journal of Medicine and Dentistry)
Background: Chronic pain is a known complication of hernia repair, yet little data are document its incidence or impact on the patient's quality of life. The purpose of this study was to investigate the prevalence of chronic pain after hernia repair, identify the main predictors, and assess the long-term outcomes among those patients.